The effect of Amine modification on siRNA delivery of redox-responsive PEGylated amphiphilic micellar nanoparticles for triple negative breast cancer therapy - Fatemeh Mehradnia; Cameron Alexander (University of Huddersfield Press, 2022)
We developed a set of methoxypoly (ethyleneglycol)-co-poly(N3-ε-caprolactone) (mPEG-N3PCL)copolymers with different types of amine linkers and investigated the contribution of the introduced amino linker to the gene delivery efficiency of nanoparticles. The nanoparticles were crosslinked from the caprolactone regions with a redox-responsive linker. Formulation variables including Redox-crosslinking and N:P ratio were examined to obtain nanoparticles with optimal size and highest siRNA entrapment efficacy (EE). The nanoparticles were characterized by DLS, and nanodrop UV-vis spectroscopy. Nanoparticle size, polydispersity index and siRNA entrapment efficacy were found to depend on the all the examined formulation variables specially the N:P ratio. The formulation with N:P ratio of 5 with56.13 nm in size and 92.24% EE was chosen as the optimal formulation. Controllable size, loading efficiency and release pattern by redox-responsivity make this class of novel carriers a promising candidate for tumour targeted gene delivery applications.